Let { c n } n ∈ N and { s n } n ∈ N be two real sequences such that c 0 = 1 , s 0 = 0 and ∀ n ∈ N :
⎩ ⎪ ⎨ ⎪ ⎧ c n + 1 = s n c 2 n = 2 c n 2 − 1 s 2 n = 2 s n c n
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The first few values of c n and s n seems to imply that c n = ℜ ( e − 2 n π i ) = cos ( − 2 n π ) and s n = ℑ ( e − 2 n π i ) = sin ( − 2 n π ) . Let us prove the claim satisfies the three equation given.
Equation 1: c n + 1 = cos ( − 2 ( n + 1 ) π ) = cos ( 2 ( n + 1 ) π ) = cos ( 2 π + 2 n π ) = sin ( − 2 n π ) = s n
Equation 2: c 2 n = cos ( − ( n + 1 ) π ) = 2 cos 2 ( − 2 ( n + 1 ) π ) − 1 = 2 c n 2 − 1
Equation 3: s 2 n = sin ( − ( n + 1 ) π ) = 2 sin ( − 2 ( n + 1 ) π ) cos ( − 2 ( n + 1 ) π ) = 2 s n c n
Problem Loading...
Note Loading...
Set Loading...
Since s 0 = 0 and c n + 1 = s n , c 1 = 0 .
Since c n + 1 = s n , c 2 n + 1 = s 2 n . Therefore, s 2 n = 2 s n c n becomes c 2 n + 1 = 2 c n + 1 c n after substitution.
Since c 2 n + 1 = 2 c n + 1 c n , c 2 ( n + 1 ) + 1 = 2 c ( n + 1 ) + 1 c ( n + 1 ) , or c 2 n + 3 = 2 c n + 2 c n + 1 . Substituting c n + 1 = c n c 2 n + 1 from c 2 n + 1 = 2 c n + 1 c n gives c 2 n + 3 = 2 c n + 2 c n c 2 n + 1 , which means c 2 n + 1 is a factor of c 2 n + 3 . (In other words, an odd term of c is a factor on the next odd term of c .) Since c 1 = 0 , all odd terms of c have a factor of 0 , meaning all odd terms of c are 0 , so c 2 n + 1 = 0 .
Since c 2 n = 2 c n 2 − 1 , and c 2 n + 1 = 0 , then all terms of c with exactly one factor of 2 are 2 ( 0 ) 2 − 1 = − 1 , so c 4 n + 2 = − 1 .
Since c 2 n = 2 c n 2 − 1 , and c 2 n + 1 = 0 , then all terms of c with exactly two factors of 2 are 2 ( − 1 ) 2 − 1 = 1 , and all terms with more than two factors of 2 are also 2 ( 1 ) 2 − 1 = 1 , so c 4 n = 1 .
Therefore, the terms of c cycle through the terms ( 0 , − 1 , 0 , 1 ) for a 2 p period of 2 p = 4 , so p = 2 .
Since c n + 1 = s n and the terms of c cycle through the terms ( 0 , − 1 , 0 , 1 ) , the terms of s cycle through the terms ( − 1 , 0 , 1 , 0 ) .
The sum S = ∑ n = 0 ∞ p n c n p + s n p = 1 1 + 0 + 2 − 1 + 0 + 4 1 + 0 + 8 − 1 + 0 + … = 1 − 2 1 + 4 1 − 8 1 + … = 1 − 2 1 ( 1 − 2 1 ( 1 − 2 1 ( 1 …
Substituting S into itself gives S = 1 − 2 1 S , and solving for S gives S = 3 2 . This means a = 2 and b = 3 , and a + b = 2 + 3 = 5 .